Efeito de compostos orgânicos de selênio em modelos experimentais de câncer e diabetes mellitus - Barbosa, Nilda Berenice de Vargas (2006)
This study was designed to determine the effect of organoselenium compounds on experimental models of cancer and diabetes. In mammary carcinogenesis induced by N-nitroso-N-methylurea (NMU, 3 doses of 50 mg/kg, i.p.), it was observed that the use of diet supplemented with diphenyl diselenide (1ppm, 7 months) was efficient in increase the latency to tumor onset and in reduce mammary tumor incidence and total number of tumors induced by NMU. The use of diet supplemented with diphenyl diselenide did not cause toxic effects in animals such as loss of body weight and alterations in hepatic and renal markers. These results suggest that diphenyl diselenide compound exhibited low toxicity even when supplemented by long time period. The both antioxidant and pro-oxidant properties of selenium may be linked to its anti-carcinogenic activity. In this context, our results indicated that antioxidant property exhibited by diphenyl diselenide can contribute for its protective effect against mammary carcinogenesis. In fact, the diet supplemented with diphenyl diselenide normalized superoxide dismutase (SOD) activity and elevated blood, hepatic and spleenic vitamin C levels in NMU treated animals. On experimental models of diabetes mellitus two treatments using organo selenium were carried out: (1) animals were treated with diphenyl diselenide and ebselen (1 mg/kg, s.c.) by 3 months after diabetes induction; (2) animals were treated with a diet supplemented with diphenyl diselenide (10 ppm) after the wean phase at the end of experimental period. Diabetes was induced with a single dose streptozotcin (STZ) (50 mg/Kg, i.p.). In model 1, it was observed that only diphenyl diselenide treatment caused significant reduction in hyperglycemia induced by STZ. This effect of diphenyl diselenide was accompanied by a reduction in the levels of glycated proteins, which were elevated in diabetic rats. Treatment with diphenyl diselenide increased SOD activity and vitamin C levels that were decreased in STZ treated rats. Of particular importance, diphenyl diselenide treatment promoted per se an increase in hepatic, renal and blood reduced glutathione (GSH) levels in animals. Similary, diphenyl diselenide caused an increase in hepatic and renal GSH levels in STZ treated rats. The STZ treatment caused a decrease in hepatic δ-ALA-D activity, which was normalized by diphenyl diselenide and ebselen treatments. This reduction in δ-ALA-D activity was not observed in renal enzyme. In model 2, it was observed that the use of diet supplemented with 10 ppm of diphenyl diselenide did not produce significant toxicity and reduced significantly the mortality index caused by STZ administration. The antioxidant property of diphenyl diselenide can be associated with this protective effect, since pro-oxidative action of STZ is linked to destruction process of cells β pancreatics. As observed in model 1, the use of diet supplemented with diphenyl diselenide reduced the alterations in antioxidant defenses induced by STZ and caused per se an increase in hepatic and blood -SH levels of animals. STZ treatment caused a decrease in hepatic δ-ALA-D activity, which was restored by the use of diet supplemented with diphenyl diselenide. The activity of renal δ-ALA-D enzyme was not modified in diabetic rats. In summary, our findings suggest that diphenyl diselenide can be considered a compound with significant therapeutic value on treatment of cancer and diabetes. However, further studies are needed to elucidate the mechanism(s) of action and the efficacy of compound as anti-diabetogenic and anticarcinogenic agent.